2014
DOI: 10.1007/s12012-014-9248-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa Supplementation to Exercise Training in a Novel Model of Physiological Cardiac Hypertrophy

Abstract: Exercise training is employed as supplementary therapy to patients with heart failure due to its multiple beneficial cardiac effects including physiological remodeling of the heart. However, precautions might be taken for the concomitant high oxidant release. Nigella sativa (NS) has been found to induce cardiac hypertrophy and enhance cardiac function. Combination of NS supplementation and exercise training might induce a safer model of cardiac hypertrophy. Our aim was to study biomarkers associated with cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…However changes in serum Nesfatin-1 concentrations were not significant. These findings were in accordance of findings of two animal studies; in one study by Khalawi AA [25] Nigella sativa oil improved hypothyroid status and decreased serum TSH concentrations in rats; in other animal study by Al-Asoom et al [28] daily oral administration of 800 mg/kg Nigella sativa in male Wistar rats reduced serum thyroxine concentrations. However in our study, for the first time, we clearly demonstrated its beneficial role on improving thyroid function in human.…”
Section: Discussionsupporting
confidence: 88%
“…However changes in serum Nesfatin-1 concentrations were not significant. These findings were in accordance of findings of two animal studies; in one study by Khalawi AA [25] Nigella sativa oil improved hypothyroid status and decreased serum TSH concentrations in rats; in other animal study by Al-Asoom et al [28] daily oral administration of 800 mg/kg Nigella sativa in male Wistar rats reduced serum thyroxine concentrations. However in our study, for the first time, we clearly demonstrated its beneficial role on improving thyroid function in human.…”
Section: Discussionsupporting
confidence: 88%
“… 7 Both experimental and clinical studies showed reproducible preferable effects of long-term supplementation of NS such as antioxidation and anti-inflammation. 8 Not only this but also the intake of NS culminates in specific and favorable modulations of cardiac structure and function, 9 , 10 vascular growth and regeneration, 11 , 12 and immunoregulatory effects. 13 NS in multiple studies demonstrated favorable modifications of the glucose and lipid metabolism in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nigella sativa (Ns), which is a traditional remedy used by multiple countries in the Middle East, was found to induce cardiac hypertrophy in Wistar rats after 8 weeks of oral administration [ 8 ]. The structural, functional, and electrophysiological features of the Ns-induced cardiac hypertrophy were found normal and comparable to that induced by exercise training [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%